A compendium of PMO case studies : reflecting project business management concepts - Bolles, Dennis L.; Hubbard, Darrel G. (Holland, MI : PBMconcepts, 2012)
This book, through the included full-text case studies, provides the reader actual information on how project, program, and portfolio management offices (PMOs) are being structured and operated by current project management organizations.
Includes bibliographical refrences and index.
oif 23/06/15
Loan
Keywords: Project management; Project management -- Case studies; Management -- Case studies; Organisation -- Case studies